Redox Regulation of cAMP-Dependent Protein Kinase and Its Role in Health and Disease - Ese S. Ekhator; Marco Fazzari; Robert H. Newman (Life)
Protein kinase A (PKA) is a key regulator of cellular signaling that regulates key physiological processes such as metabolism, cell proliferation, and neuronal function. While its activation by the second messenger 3′,5′-cyclic adenosine triphosphate (cAMP) is well characterized, recent research highlights additional regulatory mechanisms, particularly oxidative post-translational modifications, that influence PKA’s structure, activity, and substrate specificity. Both the regulatory and catalytic subunits of PKA are susceptible to redox modifications, which have been shown to play important roles in the regulation of key cellular functions, including cardiac contractility, lipid metabolism, and the immune response. Likewise, redox-dependent modulation of PKA signaling has been implicated in numerous diseases, including cardiovascular disorders, diabetes, and neurodegenerative conditions, making it a potential therapeutic target. However, the mechanisms of crosstalk between redox- and PKA-dependent signaling remain poorly understood. This review examines the structural and functional regulation of PKA, with a focus on redox-dependent modifications and their impact on PKA-dependent signaling. A deeper understanding of these mechanisms may provide new strategies for targeting oxidative stress in disease and restoring balanced PKA signaling in cells.